Microstructural, mechanical, and optical characterization of a ZTA (zirconia-toughened alumina) composite after aging - Lopes, Adolfo Coelho de Oliveira (2019)
Aim: To validate a method for the synthesis of a ZTA composite (Al2O3-80%/ Zr2O- 20%) and to characterize the experimental materials topography, optical, and mechanical properties in the as-sintered condition and after a simulated low temperature degradation (LTD) aging protocol compared to a translucent Y-TZP (ZPEX). Material and methods: Experimental ZTA (ZTA ZPEX 80/20) and translucent Y-TZP (ZPEX) green-state disc-shaped specimens were obtained by uniaxial/isostatic ceramic powder pressing technique. Discs were sintered according to a preestablished protocol. After sintering, two-sided polishing was performed with diamond discs and diamond suspensions to 1 m. Thirty specimens of each group underwent an aging protocol in autoclave (20h, 134ºC and 2.2 bar). The specimens were subjected to the following characterization tests, in the as-sintered condition and aged: 1) nanoindentation testing to acquire the materials elastic modulus (E) and hardness (H); 2) interferometry was utilized to characterize topographical parameters (Sa/Sq); 3) X-ray Diffraction (XRD) to assess the tetragonal-monoclinic phase transformation; 4) scanning electron microscopy (SEM) to evaluate the homogeneity of surfaces and distribution of grains; 5) reflectance tests on white and black background to determine the Contrast Ratio (CR) and the Translucency Parameter (TP) by color difference (E) and 6) biaxial flexural strength testing according to ISO 6872:2015. Apparent density was measured using Archimedes principle. Weibull 2-p was used to calculate characteristic stress, Weibull modulus, and probability of survival (reliability) at 300, 500 and 800 MPa. Data were statistically evaluated through Repeated Measures ANOVA following post-hoc comparisons by Tukey test (p<0.05). Results and Conclusion: The proposed method was able to successfully synthetize an aging resistant ZTA ZPEX 80/20 composite, with the elastic modulus being the only decreased property after aging. For such composite, the surface roughness parameters, hardness, optical and mechanical properties were not affected by simulated LTD aging. In contrast, the translucent Y-TZP zirconia presented a significant extent of tetragonal to monoclinic phase transformation compared to ZTA composite after aging, along with significant alterations in all evaluated parameters, except for surface roughness.